A Comparative Randomized Trial of Low-Dose Versus High-Dose Streptokinase in Deep Vein Thrombosis of the Thigh - Schulman, Sam; Lockner, Dieter; Granqvist, Staffan; Bratt, Göran; Paul, Christer; Nyman, Dag (Thrombosis and Haemostasis, 1984)
Fibrinolytic treatment of acute deep vein thrombosis (DVT) of the leg with high-dose streptokinase (SK) (100,000 U/h) in 39 cases, or low-dose SK (approx 10,000 U/h) in combination with low-dose heparin in 41 cases, was studied in a prospective randomized trial. The degree of thrombolysis was similar in both groups and did not correlate with age or size of the thrombus or with fibrinogen level. The degree of late recanalization was also similar in both groups. There were however significantly more patients with postthrombotic changes in the low-dose group than in the high-dose group after a mean follow-up time of 31 and 38 months respectively. In the low-dose group 2 intracranial hemorrhages occurred (one was fatal) and one patient died of pulmonary embolism, but there were significantly less allergic side effects to SK. There were no cases of such serious side effects in the highdose group. Although low-dose SK has equal thrombolytic effect it seems inferior to high-dose SK, since it probably causes more severe hemorrhagic side-effects.
Keywords: Deep venous thrombosis; Streptokinase treatment; Low-dose-thrombolysis; Follow-up